Mavoglurant in fragile X syndrome: Results of two randomized, double-blind, placebo-controlled trials - Berry-Kravis, Elizabeth; Des Portes, Vincent; Hagerman, Randi; Jacquemont, Sébastien; Charles, Perrine; Visootsak, Jeannie; Brinkman, Marc; Rerat, Karin; Koumaras, Barbara; Zhu, Liansheng; Barth, Gottfried Maria; Jaecklin, Thomas; et al. (Science translational medicine, 2016)
Fragile X syndrome (FXS), the most common cause of inherited intellectual disability and autistic spectrum disorder, is typically caused by transcriptional silencing of the X-linked FMR1 gene. Work in animal models has described altered synaptic plasticity, a result of the up-regulation of metabotropic glutamate receptor 5 (mGluR5)-mediated signaling, as a putative downstream effect. Post hoc analysis of a randomized, placebo-controlled, crossover phase 2 trial suggested that the selective mGluR5 antagonist mavoglurant improved behavioral symptoms in FXS patients with completely methylated FMR1 genes. We present the results of two phase 2b, multicenter, randomized, double-blind, placebo-controlled, parallel-group studies of mavoglurant in FXS, designed to confirm this result in adults (n = 175, aged 18 to 45 years) and adolescents (n = 139, aged 12 to 17 years). In both trials, participants were stratified by methylation status and randomized to receive mavoglurant (25, 50, or 100 mg twice daily) or placebo over 12 weeks. Neither of the studies achieved the primary efficacy end point of improvement on behavioral symptoms measured by the Aberrant Behavior Checklist-Community Edition using the FXS-specific algorithm (ABC-C(FX)) after 12 weeks of treatment with mavoglurant. The safety and tolerability profile of mavoglurant was as previously described, with few adverse events. Therefore, under the conditions of our study, we could not confirm the mGluR theory of FXS nor the ability of the methylation state of the FMR1 promoter to predict mavoglurant efficacy. Preclinical results suggest that future clinical trials might profitably explore initiating treatment in a younger population with longer treatment duration and longer placebo run-ins and identifying new markers to better assess behavioral and cognitive benefits.